LINEAR CONGRUENT METHOD Penerapan Algoritma Linear Congruent Method Pada Pengacakan Soal Kenaikan Tingkat Karyawan Di LKP Sempoa SIP Binjai - Adhitya, Sri Ayu; Ginting, Budi Serasi; Sihombing, Marto (Universitas Sari Mutiara Indonesia, 2022)
An exam is a test conducted to see and determine a person's ability in terms of competence,knowledge and experience. By conducting an exam, an educational institution can determinewhether a student can continue to the next class or not, while in a work environment, theinstitution can determine whether a person is entitled to be accepted as a worker or can get apromotion. Based on the journal Andilala, Gunawan (2018) about the implementation of thelinear congruent method for randomizing questions in an android-based arithmetic calculationgame. Said that